Self-assessment of inters on the efficiency of online preparation for the licensed integrated exam "Krok 3. General medical training" in a pandemic COVID-19 (analysis results of anonymous survey) - Koloskova, Olena; Khilchevska, Victoria; Bilyk, Galyna (Journal of Education, Health and Sport, 2021)
An anonymous survey of interns of the specialty "Pediatrics" on the quality of training interns for the licensed integrated exam "KROK 3. General medical training" at the Department of Pediatrics and Children's Infectious Diseases of Bukovinian State Medical University was conducted using the google form. The main purpose of the survey was to assess the effectiveness of training interns for the licensed test exam "KROK 3. General medical training" in the context of distance learning. It is shown that interns positively assess the quality of training in a distance form for passing this exam. Most interns point to the effectiveness of consultations of teachers and experts of creating tests in preparation for the exam. According to 60.0% of interns, the most effective component of preparation for the LIE "KROK 3. General medical training" was training on the program of the module "Emergencies", 25.0% noted thematic consultations conducted by teachers of the department immediately before the exam, and according to 15.0% of respondents, the best component was preparation for rector's tests. The most useful and informative for interns were consultations on emergencies in pediatrics (50.0% of responses), neurology and psychiatry (20.0%), cardiology (15.0%) and radiation medicine (15.0%).